2021
DOI: 10.3390/jcm10030442
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Permanent Hypoparathyroidism and Preoperative Vitamin D Prophylaxis

Abstract: Permanent hypoparathyroidism, a feared thyroidectomy complication, leads to significant patient morbidity, medical treatment, and monitoring. This study explores whether preoperative high-dose vitamin D loading decreases the incidence of permanent hypoparathyroidism. In a subgroup analysis, the study examines the predictive utility of day 1 parathyroid hormone (PTH) in permanent hypoparathyroidism. Patients (n = 150) were previously recruited in the VItamin D In Thyroidectomy (VIDIT) trial, a multicentre, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…According to a previous study, the incidence of permanent hypoparathyroidism, defined as PTH < 10 pg/mL at 1‐year postthyroidectomy, was 1.9%. Similar to our results, Kannan et al showed lower rates of permanent hypoparathyroidism in the intervention group compared to the control group, but there was no statistically significant difference 36 . However, we could not find studies in the literature that found opposing results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to a previous study, the incidence of permanent hypoparathyroidism, defined as PTH < 10 pg/mL at 1‐year postthyroidectomy, was 1.9%. Similar to our results, Kannan et al showed lower rates of permanent hypoparathyroidism in the intervention group compared to the control group, but there was no statistically significant difference 36 . However, we could not find studies in the literature that found opposing results.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our results, Kannan et al showed lower rates of permanent hypoparathyroidism in the intervention group compared to the control group, but there was no statistically significant difference. 36 However, we could not find studies in the literature that found opposing results. Therefore, we believe that preoperative calcium and vitamin D supply has no clinical significance on permanent hypoparathyroidism.…”
Section: Permanent Hypoparathyroidismmentioning
confidence: 60%
“…Hypoparathyroidism and hypocalcemia are well-documented consequences of thyroidectomy. The symptoms of hypoparathyroidism range from no symptoms to mild numbness and tingling, muscle spasms, tetany, seizures, life-threatening laryngospasm, and cardiac arrhythmias ( 1 , 2 ). These symptoms not only prolong the hospital stay but also lead to increased costs for additional testing and treatment ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the introduction of new intraoperative modalities aimed at preserving intraoperative parathyroid function has been reported ( 4 , 5 ). The literature also discusses using preoperative VD or calcium (Ca) supplementation ( 1 , 3 , 6 ), as well as various postoperative Ca management strategies ( 7 , 8 ), to address this issue. However, evidence supporting these interventions, including those involving natural and active VD (calcitriol or alfacalcidol), remains inconclusive ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation